A short note on analysis and application of a stochastic open-ended logistic growth model. Issue 1 (1st January 2019) - Yoshioka, Hidekazu; Yaegashi, Yuta; Yoshioka, Yumi; Tsugihashi, Kentaro
ABSTRACT: A minimal stochastic generalization of a deterministic open-ended logistic growth model is proposed for efficiently describing the biological growth of individual organisms under natural environment. The model is a system of stochastic differential equations. Its unique solvability in a strong sense is proven, and the behaviour of the solution is analysed. The presented model is then applied to the migratory fish Plecoglossus altivelis altivelis ( P. altivelis, Ayu) having a one-year life history based on the data sets collected in 2017 and 2018.